Association of CBC and CBC-derived inflammatory markers with depression and post-diabetes mellitus depression: A large cohort NHANES study spanning 2011–2020 - Wen Chen; Fasheng Deng (Archives of Gerontology and Geriatrics Plus)
Background: Inflammation promotes the risk of depression-related diseases but remains controversial. Therefore, this study investigated the association between complete blood count (CBC)/CBC-derived inflammatory markers and depression/post-diabetes mellitus (DM) depression. Method: Initially, based on NHANES database during 2011-2020, 17,628 participants were included to construct generalized linear models (GLMs) and restricted cubic spline (RCS) curves to explore associations and dose-response relationship between CBC/CBC-derived inflammatory markers and depression, respectively. Furthermore, 2,197 DM participants were selected to build GLMs and RCS curves to investigate associations and dose-response between CBC/CBC-derived inflammatory markers and post-DM depression, respectively. Result: After GLMs and RCS curves analyses, we found that high CBC inflmmatory markers including white blood cells (WBC), lymphocytes, neutrophils and red blood cell distribution width (RDW) were positively association and linear dose-response relationships with depression. CBC-derived inflammatory marker like systemic immune inflammation index (SII) was association with the risk of developing depression, exhibiting a nonlinear dose-response relationship. Additionally, high WBC increased the risk of having post-1 type DM (T1DM) with nonlinear dose-response relationship, while high monocytes resulted in a susceptibility to post-2 type DM (T2DM) depression with linear relationship. Conclusion: The association of CBC/CBC-derived inflammatory markers with depression/post-depression suggested that inflammtion contributed to depression-related diseases.